Protective properties of extracellular vesicles in sepsis models: a systematic review and meta-analysis of preclinical studies - Shujun Yang; Kanglong Zhang; Jingyu Hou; Xin Liu; Daishi Xu; Xuxiang Chen; Shuangmei Li; Yinghui Hong; Changqing Zhou; Hao Wu; Guanghui Zheng; Chaotao Zeng; et al. (Journal of Translational Medicine, 2023)
Abstract Background Multiple preclinical studies have reported a beneficial effect of extracellular vesicles (EVs), especially mesenchymal stem cells derived EVs (MSC-EVs), in the treatment of sepsis. However, the therapeutic effect of EVs is still not universally recognized. Therefore, we conducted this meta-analysis by summarizing data from all published studies that met certain criteria to systematically review the association between EVs treatment and mortality in animal models of sepsis. Methods Systematic retrieval of all studies in PubMed, Cochrane and Web of Science that reported the effects of EVs on sepsis models up to September 2022. The primary outcome was animal mortality. After screening the eligible articles according to inclusion and exclusion criteria, the inverse variance method of fixed effect model was used to calculate the joint odds ratio (OR) and 95% confidence interval (CI). Meta-analysis was performed by RevMan version 5.4. Results In total, 17 studies met the inclusion criteria. Meta-analysis of those studies showed that EVs treatment was associated with reduced mortality in animal models of sepsis (OR 0.17 95% CI: 0.11,0.26, P < 0.001). Further subgroup analysis showed that the mode of sepsis induction, the source, dose, time and method of injection, and the species and gender of mice had no significant effect on the therapeutic effect of EVs. Conclusion This meta-analysis showed that MSC-EVs treatment may be associated with lower mortality in animal models of sepsis. Subsequent preclinical studies will need to address the standardization of dose, source, and timing of EVs to provide comparable data. In addition, the effectiveness of EVs in treating sepsis must be studied in large animal studies to provide important clues for human clinical trials.